(untitled) (Research, Society and Development, 2020)
Malignant oral neoplasms have great relevance because they represent one of the main causes of death in the world. Squamous cell carcinoma is its most frequent form, but reports in the retromolar region are rare when compared to other oral sites. The objective of this work is to demonstrate the diagnosis and conduct in the case of a patient participating in the Oral Injury extension project (LeBu) at the State University of Maringá - PR/BR. Male patient, 67 years old, a heavy smoker for about 50 years, alcoholic, attended the university with an ulcer in the right lower retromolar region of brownish-white color, with approximately 3 to 4 mm, irregular shape, and rough surface. A biopsy was performed in the lesion region, collecting a fragment of approximately 2 mm, which was referred for histopathological examination, resulting in a diagnosis of moderately differentiated, invasive squamous cell carcinoma. The patient was referred for medical oncological, surgical, and chemotherapy treatment, remaining under dental monitoring throughout the treatment and later with scheduled returns. After 4 years of follow-up, the patient is in good general physical condition, with no signs of recurrence, orally rehabilitated, even quitting the smoking habit. Thus, it is concluded that the diagnosis and treatment of head and neck neoplasms lacks a multidisciplinary view, being the dental surgeon of great importance both for the diagnosis of these injuries, as well as in the prevention and treatment of injuries that may arise from or after the treatment.